Answer:
<em>22.41 + 8.9</em><em>=</em><em> </em><em>31.31</em>
<em>hope this helps</em><em> </em><em><</em><em>3</em>
Answer:the nth term of the sequence, Tn= -3n +12
Step-by-step explanation:
The nth term of an arithmetic progression is given as
Tn= a+ (n-1) d
where a= first term
and d = common difference
In this sequence, 9, 6 ,3 ,0, -3, -6 we can see that the number is decreasing by 3
The first term, a= 9
and common difference, d = -3
using our formulae
Tn= a+ (n-1) d
Tn= 9 + ( n-1) -3
Tn=9- 3n+ 3
Tn= -3n +12
Answer:
1) yes
2) no
3) yes
4)no
5)no
Step-by-step explanation:
Answer:
translation, rotation
Step-by-step explanation:
A translation is sliding around or moving around/shifting so the first one is translation. A rotation is spinning it around to a different angle so the second is a rotation. Hope this helps!!
Answer:
Option (c) "
"
Step-by-step explanation:
The given equation is :
q = c4(h + r)
We need to solve it for r.
Dividing both sides of the given equation by 4c.
![\dfrac{q}{4c}=\dfrac{4c}{4c}(h+r)\\\\(h+r)=\dfrac{q}{4c}](https://tex.z-dn.net/?f=%5Cdfrac%7Bq%7D%7B4c%7D%3D%5Cdfrac%7B4c%7D%7B4c%7D%28h%2Br%29%5C%5C%5C%5C%28h%2Br%29%3D%5Cdfrac%7Bq%7D%7B4c%7D)
Now, subtract h both sides of the equation.
![h+r-h=\dfrac{q}{4c}-h\\\\r=\dfrac{q}{4c}-h](https://tex.z-dn.net/?f=h%2Br-h%3D%5Cdfrac%7Bq%7D%7B4c%7D-h%5C%5C%5C%5Cr%3D%5Cdfrac%7Bq%7D%7B4c%7D-h)
Hence, this is the required solution.